فعالية برنامج قائم على البرمجة اللغوية العصبية لخفض الضغوط النفسية وأثره في تحسين جودة الحياة لدى معلمي المعاقين عقليا - عياد، نعيمة علي بيومي Ayyad, Naimah Ali Bayoumi; بخيت، نوال شرقاوي; إسماعيل، نبية إبراهيم Ismail, Nabih Ibrahim (جامعة المنوفية - كلية التربية, 2021)
هدفت الدراسة الحالية إلى التعرف على فاعلية برنامج قائم على البرمجة اللغوية العصبية في خفض حدة الضغوط النفسية، ومعرفة أثره في تحسين الشعور بجودة الحياة لدى معلمي التلاميذ المعاقين عقليا. وتكونت عينة الدراسة من (80) معلما ومعلمة من معلمي التلاميذ المعاقين عقليا، الذين حصلوا على درجات مرتفعة على مقياس الضغوط النفسية، ودرجات منخفضة على مقياس جودة الحياة، وتم تقسيمهم إلى مجموعتين: مجموعة تجريبية تضم (40) معلما ومعلمة، ومجموعة ضابطة تضم (40) معلما ومعلمة. واستخدمت الباحثة؛ مقياس الضغوط النفسية لدى معلمي التلاميذ المعاقين عقليا (إعداد الباحثة)، ومقياس جودة الحياة لدى معلمي التلاميذ المعاقين عقليا (إعداد الباحثة)، وبرنامج إرشادي قائم على فنيات البرمجة اللغوية العصبية (إعداد الباحثة). وأسفرت نتائج الدراسة عن وجود فروقا دالة إحصائيا عند مستوى (0.01) بين متوسطي درجات المجموعة التجريبية في كل بعد من أبعاد مقياس الضغوط النفسية لدى معلمي التلاميذ المعاقين عقليا في القياسين القبلي والبعدي، لصالح القياس البعدي. وعدم وجود فروق ذات دلالة إحصائية بين متوسطي درجات المجموعة التجريبية على مقياس الضغوط النفسية في القياسين البعدي والتتبعي (بعد شهرين من تطبيق البرنامج).. ووجود فروق دالة بين عند مستوى (0.01) بين متوسطي درجات معلمي التلاميذ المعاقين عقليا على مقياس جودة الحياة في القياسين القبلي والبعدي، لصالح القياس البعدي. كما أظهرت عدم وجود فروق ذات دلالة إحصائية بين متوسطي درجات المعلمين في القياسين البعدي والتتبعي لجودة الحياة.
The current study aimed at probing the effectiveness of program based on NLP in reducing psychological stress and its impact on improving quality of life among Mentally Retarded Pupils' Teachers. The sample of the study consisted of (80) male and female Teachers who got the highest degrees in psychological stress scale and the lowest degrees in quality of life scale, the participants were categorized into two equal groups: an experimental group, and a control one , each of which consisted of (40) teachers. The researcher has used the psychological stress scale and quality of life scale to Mentally Retarded Pupils' Teachers and a program based on NLP both of them (prepared by the researcher) , The results of the research revealed There were statistically significant differences at level (0.01) between the mean degrees of the experimental group in psychological stress scale in the pre and post measurements, in favor of the post measurement. There were no statistically significant differences between the mean scores of the experimental group in the psychological stress scale. In in the post and tracer measures. And , It also Showed that there were Statistically significant differences at level(O.Ol) between the mean degrees of the experimental group between the mean degrees of teachers on the quality of life scale in the pre and post measurements, in favor of the post measurement. It also showed that there were no statistically significant differences between the mean scores of teachers in the post and tracer measures of quality of life. There is a good effect of N.L.P. program in reducing psychological stress which led to an improvement in the quality of life among Mentally Retarded Pupils' Teachers. And this improvement continues during the follow-up period.
ورقة بحثية مشتقة من رسالة دكتوراه.
Keywords: التربية الخاصة -- الضغوط النفسية -- جودة الحياة -- ذوي الهمم